A meta-analysis of the effect of education on social capital - Huang, Jian [Verfasser]; Maassen van den Brink, Henriëtte [Verfasser]; Groot, Wim [Verfasser] (My University, 2009)
"To assess the empirical estimates of the effect of education on social trust and social participation - the basic dimensions of individual social capital - a meta-analysis is applied, synthesizing 154 evaluations on social trust, and 286 evaluations on social participation. The publication bias problem is given special emphasis in the meta-analysis. Our statistical synthesis confirms that education is a strong and robust correlate of individual social capital. The meta-analysis provides support for the existence of a relative effect of education on social participation, and of a reciprocity mechanism between the dimensions of social capital. The analysis also suggests that the erosion of social participation during the past decades has coincided with a decrease of the marginal return to education on social capital. Finally, we find differences in the return to education between genders, between US and other nations, and variations for different education attainments." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.6 Human Capital; T 1.1 Empirische Berufsbildungsforschung; Bildungsertrag; Humankapital; Sozialkapital; Empirische Forschung; Metaanalyse